Efficacy of coronavirus disease 2019 vaccines in patients with rheumatic diseases - Fatih Taştekin; Meltem Taşbakan; Candan Çiçek; Mehmet Soylu; Figen Yargucu Zihni (Archives of Rheumatology, 2023)
Objectives: In this study, we report the immune response to the BNT162b2 vaccine and CoronaVac vaccine after a two-dose vaccination and the effects of conventional drugs, immunosuppressive drugs, and new-generation therapies on vaccine responses in patients with rheumatic and musculoskeletal diseases (RMDs). Patients and methods: This is a prospective observational study conducted with 94 patients (65 males, 29 females; mean age: 42.7±12.1 years; range, 19 to 69 years) between May 2021 and January 2022. The immunogenicity of the two-dose regimens of the BNT162b2 and CoronaVac vaccines in adult patients with RMD was analyzed according to disease and treatments. Serum immunoglobulin G antibody levels against SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) spike proteins were measured four weeks after the second dose of vaccines. Results: Patients on regimens including mycophenolate, rituximab, and steroids were less likely to develop an antibody response (p=0.001, p=0.06, and p=0.001, respectively). Impairment of vaccine response by other conventional disease-modifying antirheumatic drugs and by anti-tumor necrosis factor treatments was not shown. Younger participants appeared more likely to develop an antibody response. The CoronaVac vaccine was less likely to develop an antibody response compared to the BNT162b2 vaccine (p=0.002). Systemic lupus erythematosus and vasculitis had the lowest antibody titers compared to other RMDs. Conclusion: Patients receiving mycophenolate mofetil, rituximab, and steroids should be warned about the risk of a suboptimal vaccine response. If possible, vaccination strategies should be changed, and the dose modification of drugs should be made during the vaccination. Further studies are required to determine the responses to SARS-CoV-2 vaccination and optimization of vaccine response in patients with RMDs.